The state of the art in intrusion prevention and detection - Pathan, Al-Sakib Khan. (London ; Boca Raton : CRC Press, 2014)
"This book analyzes the latest trends and issues about intrusion detection systems in computer networks and systems. It examines wired, wireless, and mobile networks; next-generation converged networks; and intrusion in social networks. Topics covered include new techniques and research on intrusion detection schemes, intrusion prevention schemes, tracing back mobile attackers, secure routing with intrusion prevention, anomaly detection, AI based techniques; physical intrusion in wired and wireless networks; and agent-based intrusion surveillance, detection, and prevention"--
Includes bibliographical references and index.
Keywords: Computer security; Computers -- Access control; Computer networks -- Security measures; COMPUTERS / Networking / General; COMPUTERS / Security / General